Metabolomics Reveal the Regulatory Effect of Polysaccharides from Fermented Barley Bran Extract on Lipid Accumulation in HepG2 Cells - Yan-Sheng Zhao; Xin-Meng Tong; Xue-Mei Wu; Juan Bai; Song-Tao Fan; Ying Zhu; Jia-Yan Zhang; Xiang Xiao (Metabolites, 2023)
Barley bran has potential bioactivities due to its high content of polyphenols and dietary fiber, etc. Fermentation has been considered as an effective way to promote the functional activity of food raw materials. In this study, polysaccharides from barley bran extract fermented by Lactiplantibacillus plantarum dy-1 (FBBE-PS) were analyzed, and its effects on lipid accumulation and oxidative stress in high-fat HepG2 cells induced by sodium oleate were evaluated. The results showed that the molecular weight decreased and monosaccharide composition of polysaccharides changed significantly after fermentation. In addition, 50 μg/mL FBBE-PS could reduce the triglyceride (TG) content and reaction oxygen species (ROS) level in high-fat HepG2 cells by 21.62% and 30.01%, respectively, while increasing the activities of superoxide dismutase (SOD) and catalase (CAT) represented by 64.87% and 22.93%, respectively. RT-qPCR analysis revealed that FBBE-PS could up-regulate the lipid metabolism-related genes such as ppar-α, acox-1 and cpt-1α, and oxidation-related genes such as nrf2, ho-1, nqo-1, sod1, cat, etc. The metabolomics analysis indicated that FBBE-PS could alleviate lipid deposition by inhibiting the biosynthesis of unsaturated fatty acids, which is consistent with the downregulation of scd-1 expression. It is demonstrated that fermentation can alter the properties and physiological activities of polysaccharides in barley bran, and FBBE-PS exhibited an alleviating effect on lipid deposition and oxidative stress in high-fat cells.